1995
DOI: 10.4319/lo.1995.40.1.0195
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bacterial growth in response to photochemical transformation of dissolved organic matter

Abstract: We tested the hypothesis that light, especially UV‐B radiation, increases the availability of dissolved organic matter (DOM) to pelagic bacteria in lake water. Filtered (0.2 µm) and autoclaved humic lake water (water color 70 mg Pt liter−1, 12 mg dissolved organic C liter−1) was exposed to simulated sunlight (UV‐B, 1.14 W m−2; UV‐A, 3.87 W m−2; and PAR, 20 W m−2) for various periods of time (0–100 h). Irradiated water was then inoculated with a natural bacterial assemblage (0.6‐µm filtered water) and bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
246
1
9

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 318 publications
(266 citation statements)
references
References 11 publications
10
246
1
9
Order By: Relevance
“…Earlier, we showed that. sunlight, and especially UV-B radiation, causes DOM tcl become more available to bacteria (Lindell et al 1995), We suggest that this is due to a photolytic cleavage of high-molecular DOM into smaller moieties more available to bacteria. Thus, in addition to causing direct abiotic DIC production, light also may increase DIC production by increasing bacterial production and respiration.…”
Section: Discussionmentioning
confidence: 98%
“…Earlier, we showed that. sunlight, and especially UV-B radiation, causes DOM tcl become more available to bacteria (Lindell et al 1995), We suggest that this is due to a photolytic cleavage of high-molecular DOM into smaller moieties more available to bacteria. Thus, in addition to causing direct abiotic DIC production, light also may increase DIC production by increasing bacterial production and respiration.…”
Section: Discussionmentioning
confidence: 98%
“…The effective light penetration depth for production of these compounds in the open ocean was estimated to be ϳ5 m (Mopper et al 1991), close to our sampling depth of 4 m at Sta. M. Bacterial uptake of fatty acid and nitrogen-rich compounds produced from photooxidation of humic material has been observed in both freshwater and marine systems (Kieber et al 1989;Lindell et al 1995;Wetzel et al 1995;Bushaw et al 1996). Thus, given the energy constraints of the bacterial populations in the eastern North Pacific, we speculate that older, more refractory DOC may be made available for bacterial utilization and assimilation via cometabolism and/or photooxidative processes.…”
Section: Utilization Of Older Bulkmentioning
confidence: 99%
“…A totally different type of explanation considers cyanobacteria (mostly Prochlorococcus) as the organisms responsible for the uptake of labelled substrates in the light (Zubkov et al 2003, Church et al 2004, 2006, Michelou et al 2007). Finally, a relatively stronger negative impact of light on viruses and protistan grazers compared to bacteria (Sommaruga et al 1997, Pakulski et al 2007) and photochemical transformations of extant DOM (Lindell et al 1995, Benner & Biddanda 1998, Obernosterer et al 1999) have also been suggested. Based on the possible mechanisms governing bacterial responses to irradiance listed above, and the likely possibility that 2 or more of these mechanisms can be simultaneously operative, it becomes clear that we are still far from knowing what the relevant controls are.…”
Section: A Specific Example: the Question Of Light Vs Dark Incubatiomentioning
confidence: 99%